Targeted review of maximum residue levels (MRLs) for dicofol - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Marco Binaglia; Luis Carrasco Cabrera; Irene Castellan; Anna Federica Castoldi; Arianna Chiusolo; Katia Chukwubike; Federica Crivellente; Monica Del Aguila; Lucien Ferreira; et al. (EFSA Journal, 2023)
Abstract In accordance with Article 43 of Regulation (EC) 396/2005, EFSA received a request from the European Commission to review the existing maximum residue levels (MRLs) for the non‐approved active substance dicofol in view of the possible lowering of the MRL. EFSA investigated the origin of the current EU MRLs. All existing EU MRLs reflect previously authorised uses in the EU or are based on obsolete Codex Maximum Residue Limits. Furthermore, in view of the limitations of the toxicological dataset and related uncertainties, the existing toxicological reference values derived at the EU level cannot be confirmed for dicofol. EFSA therefore proposed lowering all existing EU MRLs for dicofol to the limit of quantification.